Religijność głęboko wierzącej młodzieży - Klimski, Wojciech (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
The article presents the characteristics of the religiousness of high school and university students who declared themselves deeply religious in sociological research from 2017. The value of the study is that it shows different dimensions of religiousness. There are no newer studies of this type. The authors were interested in such dimensions of religiousness as the global attitude to faith, religious ideology, religious practices and morality, and the sense-creating role of religion. The religiousness of deeply believing individuals was also compared with the religiousness of believers who are undecided but attached to religious tradition. The analysis shows that the category of deep believers is not numerous, so their religiousness is not common. Some of its dimensions are characterised by a high level of conformity to the teaching of the Church, and others are marked by selectivity. This is the first type of religiousness most widespread among deeply believing people. A minority of them represent a different type – church religiousness. It is not selective and reflects the institutional model of piety as fully as possible. These two types of religiousness can also be forms of religious ethos and fit into the conditions of social and cultural pluralism in Poland.